Analysis of Chemical Properties of Edible and Medicinal Ginger by Metabolomics Approach. (1st October 2015) - Tanaka, Ken; Arita, Masanori; Sakurai, Hiroaki; Ono, Naoaki; Tezuka, Yasuhiro
Abstract : In traditional herbal medicine, comprehensive understanding of bioactive constituent is important in order to analyze its true medicinal function. We investigated the chemical properties of medicinal and edible ginger cultivars using a liquid-chromatography mass spectrometry (LC-MS) approach. Our PCA results indicate the importance of acetylated derivatives of gingerol, not gingerol or shogaol, as the medicinal indicator. A newly developed ginger cultivar, Z. officinale cv. Ogawa Umare or "Ogawa Umare" (OG), contains more active ingredients, showing properties as a new resource for the production of herbal medicines derived from ginger in terms of its chemical constituents and rhizome yield.